Urgency of Regulation on Bankruptcy Applicants for Regional Public Companies - Thufail Rozaan; Sukarmi Sukarmi; Reka Dewantara (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2025)
The absence of a clear legal framework governing the authority to initiate bankruptcy proceedings against Regional Public Companies (Perusahaan Umum Daerah, or Perumda) has resulted in a normative gap that undermines legal certainty and institutional accountability. This article explores the urgency of establishing a new normative order (ius constituendum) concerning eligible bankruptcy petitioners against Perumda by critically examining its legal standing within Indonesia's economic and public law system. Employing a normative juridical method that integrates statutory and conceptual approaches, this research applies systematic and grammatical interpretations to relevant primary and secondary legal sources. The findings reveal that the lack of explicit legal norms not only exposes Perumda to arbitrary actions and potential misuse of authority but also jeopardizes creditor protection and public service continuity. The study concludes by advocating for a firm regulatory framework that delineates clear procedural safeguards, thereby reinforcing the function of law as an instrument of justice and public interest protection.